Mindfulness as Stress Management in Improving the Performance of Female Workers - Sari, Adelin; Yoenanto, Nono Hery; Huda, Cholicul (Jurnal Keperawatan Muhammadiyah, 2025)
Working women often face various pressures, both from professional demands in the workplace and from the domestic roles they carry out simultaneously. These pressures can lead to stress, which in turn can adversely affect performance. This study aims to examine the effectiveness of mindfulness as a stress management strategy in improving the performance of working women. Working women tend to experience higher levels of stress compared to mothers who do not work. The research method used was a quasi-experimental design with a pretest–posttest format without a control group. The sample consisted of 15 working women selected through purposive sampling. The instruments employed included the Perceived Stress Scale (PSS-10) and a Worker Performance Scale. The intervention consisted of mindfulness training conducted over two weeks, comprising four sessions focused on exercises that cultivate full attention to thoughts, feelings, and the body. Data analysis results indicated a significant decrease in stress scores following the intervention, as well as an improvement in performance scores. A Wilcoxon signed-rank test revealed a statistically significant difference between pretest and posttest (p < 0.05), demonstrating that mindfulness is effective in reducing stress. Thus, mindfulness has proven to be an effective stress management strategy that can enhance performance, particularly for women facing dual roles. The study recommends implementing mindfulness as part of employee wellbeing programs, especially in work environments with high psychological demands.